2010
DOI: 10.1111/j.1365-2028.2009.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing secondary seed removers: results from camera trapping

Abstract: This paper reports the results of the first study on secondary seed removal of seeds dispersed by Sykes’ monkeys (Cercopithecus albogularis) using camera traps in Africa. Patterns of primary seed dispersal are often superimposed by secondary conveyance, emphasising the need to study these secondary processes carefully. As the agents and mechanisms of seed dispersal are often concealed, being carried out by cryptic or nocturnal animals in dense vegetation, camera trapping was deemed a viable means to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Cricetomys spp. have mostly been considered as seed predators rather than seed dispersers (Guedje et al 2003, Kankam & Oduro 2009, Seufert et al 2010, but results of this study confirm previous findings in which giant-pouched rat stored seeds of Carapa procera and Detarium microcarpum in their burrows (Debroux 1998, Bationo et al 2002.…”
Section: Seed Dispersal By Rodents In Africa 655supporting
confidence: 93%
“…Cricetomys spp. have mostly been considered as seed predators rather than seed dispersers (Guedje et al 2003, Kankam & Oduro 2009, Seufert et al 2010, but results of this study confirm previous findings in which giant-pouched rat stored seeds of Carapa procera and Detarium microcarpum in their burrows (Debroux 1998, Bationo et al 2002.…”
Section: Seed Dispersal By Rodents In Africa 655supporting
confidence: 93%
“…Seed dispersers of most plant species and their effect on seedling establishment remain unknown—a problem that is particularly acute for rare species in remote localities. Motion‐activated cameras offer new opportunities to document interactions between plants and animal seed dispersers (Midgley, White, Johnson & Bronner, ; Nyiramana, Mendoza, Kaplin & Forget, ; Seufert, Linden & Fischer, ).…”
Section: Introductionmentioning
confidence: 99%
“…While recognised as seed predators, studies from Asia, Australia and Africa have shown that suids also pass seeds intact through the digestive system (Corlett, ; Castley et al ., ; Westcott et al ., ) and act as important seed dispersers in some habitats (Kerley, Mclachlan & Castley, ). Their role as seed dispersers in other ecosystems within Africa remains to be determined (Geldenhuys, ; Seufert, Linden & Fischer, ), but bush pigs can therefore have both beneficial and detrimental functional roles within African landscapes.…”
Section: Resultsmentioning
confidence: 99%